The Modification of Coal Fly Ash Adsorbent Using Dithizone Immobilization for Cd(II) Ions Removal - Dina Fitriana; Mudasir Mudasir; Dwi Siswanta (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
The adsorption of Cd(II) ions onto an adsorbent of dithizone-immobilized coal fly ash (DCFA) was done using batch experiments. In this study, coal fly ash was initially activated using hydrochloric acid, and then its surface was modified by dithizone. The immobilization of activated coal fly ash (ACFA) with dithizone has been carried out to increase the adsorption capacity as the adsorbent of Cd(II) ions. The synthesized adsorbents (DCFA and ACFA) were characterized by FT-IR, XRD, TGA-DTA, adsorption-desorption N2 (BET), and SEM to confirm the successful immobilization of dithizone on the activated coal fly ash. The adsorption parameters, such as pH, adsorbent dosage, contact time, and initial concentration of Cd(II) ions on the adsorption efficiency, were optimized. Optimal adsorption was achieved at pH 7, an adsorbent dosage of 0.1 g, a contact time of 75 minutes, and an initial Cd(II) concentration of 50 mg L-1. The results showed that the adsorption kinetics were found to follow a pseudo-second-order kinetic model, and their adsorption isotherms were best described by the Langmuir model. Kinetics and adsorption isotherm studies suggested that the capacity, equilibrium constant, and energy of the DCFA in adsorbing Cd(II) ions are improved compared to those of non-immobilized ACFA. A sequential desorption study using different solvents of H2O, KNO3, HONH2HCl, and Na2EDTA revealed that binding Cd(II) ions to the adsorbents primarily involves chemisorption. The type of interaction shifts significantly from being predominantly electrostatic or ion-exchange in ACFA to primarily involving chelate complexation in DCFA.